(untitled) - Langan, John (Boston, MA, 2006)
One of the most comprehensive and well-respected books of its kind, English skills, Eighth Edition, features John Langan's crystal-clear explanations and his wide range of motivating activities and writing assignments that reinforce the four essentials of good writing: unity, support, coherence and sentence skills. English skill continues to help students succeed with its focus on paragraph writing skills in preparation for essay writing. The eighth edition adds several new features.
Keywords: English language,English language,Report writing; Rhetoric.,Grammar